PENGARUH PEMBERIAN PUPUK BOKASHI JERAMI PADI TERHADAP PERTUMBUHAN DAN HASIL SELADA DAUN (Lactuca Sativa L.) - Wulandari, Resty; Mulyati, Mulyati; Novi, Novi (STKIP PGRI Sumbar, 2013)
ABSTRACTLeaf lectuce (Lactuca sativa L.) is one of the plant have high nutricion, especially mineral to accelerate absorption to decease fever. The research aim to know the effect of paddy straw bokashi fertilizer on growth and yield of leaf lectuce in pollybag. This research was conducted in farmer field in Kayu Tanduk village, X Koto district, Tanah Datar regency from May 2013 until August in 2013. The research was design of this research was a experimental research, with Randomized Completely Design (RCD), with 6 treatment and 5 repitition. Each treatment A control (300 gr manure), B 100gr of paddy straw bokashi/pollybag, C 150 gr /pollybag, D 200 gr/pollybag, E 250 gr/pollybag, F 300 gr/pollybag. To analyze the date, used ANOVA and BNT 5% standard. The result of this research, shows that the paddy straw bokashi fertilizer input have significant effect on fresh weight of plant. But not significantly for quantity of leaf in 5% standard. The researcher conclude that straw was given with 150 gr/pollybag doce forward leaf lectuces saw increasing growth and result.Â